(untitled) - Baker, Lyndon (Northampton, 1995)
The book is divided into two parts. The first part is full of helpful suggestions for directed work with early years children. The second part is a collection of structured activities provided as a set of photocopiable worksheets with accompanying teacher's notes
Keywords: Mathematics; Study and teaching (Elementary)